A Surgeon's Guide to Obtaining Hemorrhage Control in Combat-Related Dismounted Lower Extremity Blast Injuries. Issue 10 (1st October 2016) - Radowsky, Jason S.; Rodriguez, Carlos J.; Wind, Gary G.; Elster, Eric A.
ABSTRACT: The application of lessons learned on the battlefield for timely surgical control of lower extremity hemorrhage secondary to blast injuries to the civilian practice for similar wounding patterns from industrial accidents or terrorist activities is imperative. Although simple cut-down procedures are commonly sufficient for the control of blood vessels for distal extremity traumatic amputations, high-thigh or disarticulation wounding patterns often require more complex surgical methods. The following details both the decision-making process and operative techniques for controlling hemorrhage from lower extremity blast injuries.